Cross-Cultural Adaptation of the Developmental Coordination Disorder Questionnaire 2007 for German-Speaking Countries: DCDQ-G - Kennedy-Behr, Ann; Wilson, Brenda N.; Rodger, Sylvia; Mickan, Sharon (Neuropediatrics, 2013)
Background The Developmental Coordination Disorder Questionnaire 2007 (DCDQ'07) is widely used internationally and is a useful measure to assist in the diagnosis of developmental coordination disorder. The aim of this study was to translate the DCDQ'07 into German, test the psychometric properties, and establish cutoff scores for the 5.0 to 7.11 age group.Materials and Methods A six-stage cross-cultural adaptation process was used. The psychometric properties of the DCDQ-German (DCDQ-G) were tested with a clinic sample of 55 children (mean age: 6.1 years) and community sample of 67 children (mean age: 5.6 years).Results The internal consistency was high. Specificity and sensitivity for the total sample were 52.4 and 90%, respectively. Sensitivity for the clinic sample was 72.7% and specificity was 95%. The community sample had a sensitivity of 30% and a specificity of 86.7%.Conclusion The DCDQ-G is a valid instrument for use with a clinic population in the 5.0 to 7.11 age group. Research into older age groups is ongoing.
Keywords: developmental coordination disorder; questionnaire; diagnosis; cross-cultural adaptation